Cover Picture: The Chemistry of Cyborgs—Interfacing Technical Devices with Organisms (Angew. Chem. Int. Ed. 52/2013). Issue 52 (11th December 2013) - Giselbrecht, Stefan; Rapp, Bastian E.; Niemeyer, Christof M.
<x xml:space="preserve">Abstract</x> Even after 125 years …︁ …︁ Angewandte Chemie is looking into the future, and in this last issue of the anniversary volume in particular. The cover picture of this issue is for a Review by C. M. Niemeyer et al. (page 13942 ff.) on the chemistry of cyborgs. These cybernetic organisms are chimeras of machines and living organisms. As alluded to by the adaptation of Michelangelo's famous painting, this rapidly emerging field of research and development takes advantage of chemical compounds and concepts, including, but not limited to, biocompatible polymer coatings for implants. Further Reviews are on the plasmonic synthesis of nanoparticles (C. Mirkin et al.) and the generation of pluripotent stem cells (Nobel Lecture by S. Yamanaka).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>